Marketing Communication of Masjid Jajar Boarding School in Obtaining High-achieving Prospective Students - Pambudi, Tata Luhur; Riyanto, Buddy; Itasari, Andri Astuti (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Slamet Riyadi Surakarta, 2024)
The quality of students is one of the main focuses in the continuity of an Islamic boarding school. The quality of the students will influence the conduciveness of Islamic boaring school. smoothness of teaching and learning process, achievement standards, and even influence the reputation of Islamic boaring school in the community. The lack of students with superior quality at Jajar Mosque Islamic Boarding School presents its own obstacles to Islamic boarding school in realizing its ideasThe data collection method in this scientific work is open interviews and document study. Then the collected data was analyzed using the Miles and Huberman analysis method. The problem of Jajar Mosque Boarding School in obtain outstanding prospective students is that the marketing communications implemented are less than optimal. The result of this study are to provide altenatives marketing communications to increase the number of prospective highachieving students at Masjid Jajar Islamic Boarding School supported by Kotler’s marketing communications mix theory.